Globalization, structural change and innovation in emerging economies: The impact on employment and skills - Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This paper aims to provide a critical overview of the drivers that the relevant theoretical and empirical literature suggests being crucial in dealing with the challenges an emerging country may encounter in its attempts to further catch-up a higher income status, with a particular focus devoted to the implications for the domestic labor market. In the first part of the paper, attention will be focused on structural change, capability building and technological progress, trying to map - using different taxonomies put forward by the innovation literature - the concrete ways through which an emerging country can engage a successful catching-up, having in mind that developing countries are deeply involved into globalized markets where domestic innovation has to be complemented by the role played by international technology transfer. In the second part of the paper, the focus will be moved to the possible consequences of this road to catching-up in terms of employment and skills. In particular, the prescriptions by the conventional trade theory will be contrasted with a view taking into account technology transfer, labor-saving technological progress and skill-enhancing trade.
Keywords: O14; O33; 330; catching-up; structural change; globalization; capabilities; technological transfer